A quantitative study of the influence of coprocessing of binders on the mechanical properties of paracetamol tablets - Abayomi Tolulope Ogunjimi; Gbenga Alebiowu (Universidade de São Paulo, 2010)
A 2³ factorial experimental design has been used to quantitatively study individual and interaction effects of the nature of binder (N), concentration of binder (C) and the applied pressure (P) on two mechanical properties, namely, tensile strength (TS) and brittle fracture index (BFI), of paracetamol tablets. The factorial design was also used to study the quantitative effects of coprocessing of binders on the mechanical properties. The results obtained from this study suggest that the nature (i.e. plastic/elastic) and ratio of binders coprocessed together alter the influence of C and P on TS and BFI. Utilizou-se planejamento experimental fatorial 2³ para estudar, quantitativamente, os efeitos individuais e de interação da natureza do ligante (N), concentração do ligante (C) e a pressão aplicada (P) em duas propriedades mecânicas, como forças de ruptura (TS) e índice de fragilidade (BFI) de comprimidos de paracetamol. O planejamento fatorial foi, também, empregado para estudar os efeitos quantitativos do coprocessamento de ligantes nas propriedades mecânicas. Os resultados obtidos desse trabalho sugerem que a natureza (plástica/elástica) e a proporção de ligantes coprocessados, juntas, alteram a influência de C e P em TS e em BFI.